The Use of Emotionally Focused Therapy with Separated or Divorced Couples - Allan, Robert (Canadian Journal of Counselling and Psychotherapy, 2016)
Couples with children who are separated or divorced need to develop a plan for coparenting and the lifelong shared tasks of childrearing. While legally informed programs can offer mediation, these services can miss the underlying conflict that continues to plague postseparation couple relationships and, more importantly, their children. Divorce is a process with multiple transitions for a family, and the couples who separate or divorce may have a history of negative communication patterns that have long corroded their relationship. There is a need to develop a new coparenting relationship that can serve as a foundation for the long-term. The research literature varies in understanding the impact of divorce on children, but there is consistent agreement that parental conflict does affect child maladjustment. Emotionally focused therapy (EFT) is one effective means of working with a couple who are separated or divorced. EFT is an empirically supported couples’ treatment that was developed from attachment, emotion, and systems theories. This article explores the use of Stage 1 of EFT for couples who are separated or divorced, using a case example to further illustrate the model.